DESIGN AND DEVELOPMENT OF A WEB-BASED SYSTEM FOR TRANSFORMATION AND UPLOADING OF PT XYZ CUSTOMER DATA TO THE CORETAX SYSTEM - Kania Fitriani Putri Atmaja; Eka Merdekawati (JURNAL ILMIAH EDUNOMIKA, 2026)
PT XYZ a heavy equipment distribution and service company, relies on an internal Accounting Information System (AIS) to record customer data used for output tax invoicing. Because AIS has no built-in feature to generate the XML format required by the Coretax Administration System, staff must convert data manually through Microsoft Excel, a practice prone to formatting errors and processing delays. Rather than covering every stage of the wider research project, this article narrows its scope specifically to the design, development, and implementation of Bridge XML, the web-based system built to bridge AIS and Coretax. Using a Research and Development (R&D) approach structured around the Waterfall Software Development Life Cycle (SDLC), the system was modeled through a flowchart, a context diagram, and multi-level data flow diagrams, then implemented as five interdependent modules: account registration and approval, authentication, automated XLS-to-XML conversion, structural error checking, and controlled upload with activity logging. Representative functional verification indicated that these modules operated as designed across the primary conversion, validation, and upload scenarios. The findings illustrate how a lightweight, web-based ETL (Extract-Transform-Load) architecture can be layered onto an existing AIS to satisfy an external regulatory data standard without replacing the underlying accounting system. The article closes by discussing the architectural reasoning behind each design decision, the constraints encountered during implementation, and directions for extending the system's scalability and integration depth.